2018
DOI: 10.1007/s12032-018-1191-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduced HBV cccDNA and HBsAg in HBV-associated hepatocellular carcinoma tissues

Abstract: Approximately 50% of hepatocellular carcinoma (HCC) is attributable to chronic infection with hepatitis B virus (HBV). Serum hepatitis B surface antigen (HBsAg) is an important diagnostic marker of HBV infection, whereas intrahepatic HBV covalently closed circular DNA (cccDNA) is a surrogate marker of HBV persistence. This study aimed to investigate relationships between serum HBsAg, intrahepatic HBsAg, and intrahepatic cccDNA in HBV-associated HCC. Intrahepatic HBsAg was determined by immunohistochemistry in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
1
8
1
2
Order By: Relevance
“…It is consistent with reports that there are lower viral loads in HBV infection HCC patients than in chronic HBV infection patients with cirrhosis . And, Tantiwetrueangdet et al reported that HBV cccDNA and intrahepatic HBsAg in HBV‐associated HCC tissues were significantly reduced, as compared with matched noncancerous tissues.…”
Section: Discussionsupporting
confidence: 87%
“…It is consistent with reports that there are lower viral loads in HBV infection HCC patients than in chronic HBV infection patients with cirrhosis . And, Tantiwetrueangdet et al reported that HBV cccDNA and intrahepatic HBsAg in HBV‐associated HCC tissues were significantly reduced, as compared with matched noncancerous tissues.…”
Section: Discussionsupporting
confidence: 87%
“…Three previous papers also reported the significantly reduced expression of HBsAg in HBV-associated HCC tissues compared with matched non-tumor tissues, and one paper attributed it to HBV integration in tumor cells. 29–31 However, no viral integrants were found in the tumor specimen from a patient in our study. According to the results from one of these papers that HBV receptors were deficient in tumor but over-expressed in peritumor, 30 HBV integrants in tumor tissues should be probably fewer than those in non-tumor tissues.…”
Section: Discussioncontrasting
confidence: 58%
“…The cut-off value for p53 protein positivity was a p53 staining with positive nuclei in ≥1% of cells, regardless of the staining intensity, as we previously reported [ 24 ]. The cut-off value for HBsAg protein positivity was an HBsAg staining with positive cytoplasmic staining > 1 cell in each tissue section, as we previously reported [ 26 ].…”
Section: Methodsmentioning
confidence: 99%